How ex-employee citizenship behavior is generated: From the perspective of legacy identification - Tian, Zehui; Yuan, Qinghong; Qian, Shanshan; Guo, Yanhong (Frontiers in Psychology, 2022)
The termination of employment is not the end of an organization-employee relationship. As ex-employees can provide various benefits to their former organizations, and a large number of ex-employees have accumulated in enterprises because of increased employee mobility, research on ex-employees’ contribution behavior and how it is generated are significant to organizations in making use of their ex-employees effectively and consequently improving organizational efficiency. Based on the research into organizational citizenship behavior, Study 1 extended the focus of organizational citizenship behavior research to include ex-employees, introducing the concept of ex-employee citizenship behavior. The measurement of ex-employee citizenship behavior was developed based on Hinkin’s tutorial. Using social identity theory, Study 2 discussed how ex-employee citizenship behavior is generated. A two-wave survey of 291 former employees was conducted. A hierarchical regression analysis and the bootstrap method were then applied test the hypotheses. The results showed that legacy identification was positively related to ex-employee citizenship behavior. Furthermore, the interaction between perceived organizational prestige and perceived insider status was positively related to legacy identification. Perceived organizational prestige and perceived insider status were also indirectly and interactively related to ex-employee citizenship behavior through legacy identification. The positive relationship between legacy identification and ex-employee citizenship behavior was moderated by the cooperative relationship between the current and former organizations. Additionally, the indirect positive effect of the interaction between perceived organizational prestige and perceived insider status on ex-employee citizenship behavior through legacy identification is moderated by the cooperative relationship between the current and former organizations. The theoretical and practical implications of this study were discussed. Finally, the limitations of this study were presented alongside suggestions for future research.